Naringenin Produces Neuroprotection Against LPS-Induced Dopamine Neurotoxicity via the Inhibition of Microglial NLRP3 Inflammasome Activation - Chen, Ce; Wei, Yi-Zheng; He, Xue-Mei; Li, Dai-Di; Wang, Guo-Qing; Li, Jing-Jie; Zhang, Feng (Frontiers in Immunology, 2019)
Background: Parkinson's disease (PD) is the second most prevalent central nervous system (CNS) degenerative disease and characterized by slow and progressive loss of dopamine (DA) neurons in the midbrain substantia nigra. Microglia-mediated neuroinflammation has been considered as the major central event in the process of DA neuronal loss. Thus, inhibition of neuroinflammation could possess a more viable strategy for PD treatment. Naringenin (NAR), a natural flavanoid contained in citrus fruit and grapefruits, possesses amounts of pharmacological activities. Recent studies indicated that NAR produced neuroprotection against several neurological disorders. However, the mechanisms underlying NAR-generated neuroprotection are not fully illuminated. Methods: In the present study, rat nigral stereotaxic injection of lipopolysaccharide (LPS)-induced DA neuronal loss was performed to investigate NAR-mediated neuroprotection. In addition, BV-2 and MN9D cell lines were applied to explore the underlying mechanisms. Results: NAR protected DA neurons against LPS-induced neurotoxicity. Also, NAR suppressed microglial nod-like receptor protein 3 (NLRP3) inflammasome signaling activation and the subsequent pro-inflammatory factors release. In addition, NAR-mediated DA neuroprotection was dependent on the inhibition of microglial NLRP3 inflammasome activation, as evidenced by the observations that NAR-reduced pro-inflammatory factors production and further NAR-exerted DA neuroprotection against LPS-induced neuronal damage was not discerned after microglial NLRP3 siRNA treatment. Conclusions: This study demonstrated that NAR targeted microglial NLRP3 inflammasome to protect DA neurons against LPS-induced neurotoxicity. These findings suggest NAR might hold a promising therapeutic potential for PD.